Improving Reading Skills in the English Language - Ummatov Dilzodbek Dilshodjon o’g’li; Ziyodullayev Jamshid Azamat o’gli (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Reading is one of the most essential skills in learning a foreign language, especially English. This article discusses the importance of reading skills and explains simple yet effective ways to improve them. The paper focuses on common difficulties learners face and suggests practical strategies such as vocabulary development, reading techniques, and regular practice to help students become confident and successful readers.